PERAN GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI DINAS KOPERASI DAN USAHA MIKRO KABUPATEN SUMENEP - Chamariyah; Fatimah Riswati; Moh. Bahar (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
The purpose of this study are 1). To describe the leadership style, work environment and work performance of employees at the Office of Cooperatives and Micro Enterprises of Sumenep Regency. 2) To test and analyze the leadership style and work environment level simultaneously have a significant influence on the work performance of employees at the Office of Cooperatives and Micro Enterprises of Sumenep Regency. 3) To test and analyze the leadership style and work environment partially have a significant influence on the work performance of employees in the Office of Cooperatives and Micro Enterprises of Sumenep Regency. This research is an expalanotory research, the research approach uses a quantitative approach, and Data analysis uses SPSS. The research sample was 32 people. The results showed that: 1). simultaneously, leadership style and work environment have a significant effect on the work performance of employees at the Office of Cooperatives and Micro Enterprises of Sumenep Regency. Evidenced by the results of the calculated F value of 3.218 with a significance value of 0.01, which means less than 0.05. 2). partially, leadership style and work environment have a significant effect on the work performance of employees at the Office of Cooperatives and Micro Enterprises of Sumenep Regency.